Some coral diseases track climate oscillations in the Caribbean - Randall, C. J. (Sci Rep, 2017)
Disease outbreaks continue to reduce coral populations worldwide. Understanding coral diseases and their relationships with environmental drivers is necessary to forecast disease outbreaks, and to predict future changes in coral populations. Yet, the temporal dynamics of coral diseases are rarely reported. Here we evaluate trends and periodicities in the records of three common coral diseases (white-band disease, yellow-band disease, and dark-spot syndrome) that were surveyed between 1997 and 2014 at 2082 sites throughout the Caribbean. The relationship between the periodicities of disease prevalence and El Niño Southern Oscillation (ENSO) cycles was examined using cross-wavelet analyses and convergent cross mapping (CCM). The prevalence of the diseases peaked every two to four years, and matched periodicities in ENSO conditions. CCM models suggested that environmental conditions associated with recent ENSO cycles may have influenced the patterns in disease prevalence. We also found no increasing trends in disease prevalence through time. Instead, our work suggests that the prevalence of coral diseases is dynamic and complex. The gradual increase in sea-surface temperature, a consequence of increasing greenhouse gas emissions, progressively raises the modal temperature threshold of each ENSO cycle. These dynamic cycles and the increasing modal temperatures appear to influence the dynamics of coral diseases.